Pengaruh Kepemimpinan Transformasional, Penggunaan Information and Communication Technology (ICT), dan Motivasi Kerja terhadap Kinerja Dosen Perguruan Tinggi di Kabupaten Pamekasan Madura - Dilla, Angga Riski (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2022)
The aims of this study are: (1) Explaining transformational leadership on lecturer performance. (2) Explaining the effect of using information communication technology (ICT) on lecturer performance. (3) Explaining the effect of work motivation on lecturer performance. (4) Explaining the influence of transformational leadership, use of information and communication technology (ICT) and work motivation on lecturer performance. The approach in this study uses quantitative data collection using a questionnaire/questionnaire. The population of this research is lecturers of Pamekasan Madura University with a total sample of 75 lecturers. The sampling technique in this study used proportionate random sampling. Data analysis used multiple linear regression with SPSS. The results of this study indicate that: (1) There is a positive influence of transformational leadership on lecturer performance, as evidenced by rejecting the Ho hypothesis with a sig value of 0.000